Geochemistry of Pliocene to Quaternary alkali basalts from the Huri Hills, northern Kenya - Class, Cornelia; Altherr, Rainer; Volker, F.; Eberz, Günther; McCulloch, M. T. (Chemical geology, 1994)
Pliocene to Quaternary basaltic lavas from the Huri Hills show a continuous change in eruptive style from earlier fissure-type eruptions producing extensive lava flows to later central-type activity, resulting in cinder cones and associated small lava flows. This change in eruptive style was accompanied by systematic variations in chemical composition and isotopic signature. With decreasing age, rock compositions change from alkali basalt to basanite (CIPW-normative nepheline increases from 3% to 22%). Whereas chondrite-normalised La abundances increase from ∼ 40 to 200, Yb stays almost constant at ∼ 10× chondritic. Concurrently, samples with Mg#>64 exhibit an increase in chondrite-normalised Tb/Yb and Zr/Y, as well as a decrease in Sc and Ti/Zr. Since no correlation between any of these parameters and the CaOAl2O3 ratio or Mg# is observed, the systematic temporal variations in trace-element ratios of slightly fractionated magmas can best be explained by an increasing amount of garnet in the residue of the melts. With decreasing age and increasing CIPW-normative nepheline, Huri Hills lavas show decreasing 87Sr86Sr ratios (0.7033-0.703) and increasing 143Nd144Nd (0.5129-0.51295) and 206Pb204Pb (18.7-19.3) ratios. Concurrently, ratios such as Ba/Th, K/La and Sr/Nd decrease. These covariations suggest binary mixing of two chemically and isotopically distinct end-member compositions. The first end-member, with high 206Pb204Pb ratios, is most probably derived from a plume source with HIMU affinities. The second end-member, showing low 206Pb204Pb, and high 87Sr86Sr, Ba/Nb and Sr/Nd ratios, is tentatively attributed to the lithospheric mantle but could also be a second plume component.